Keefektifan Pembelajaran Mengidentifikasi Isi Cerita Hikayat Menggunakan Media Animasi pada Siswa Kelas X SMA - Nufi Azam Muttaqin; Haryadi Haryadi; Agus Nuryatin (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Literature learning, especially the listening element, often receives little attention. One of the contributing factors is the teacher's lack of ability to present interesting learning material, which has an impact on reducing students' interest and motivation to learn in teaching and learning activities in the classroom. Literature learning, especially the listening element, needs to present interesting learning media. One of the media that can be used in literature learning, especially the listening element, is animation media. The aim of this research is to determine the level of effectiveness of using animation media in learning literary elements of listening, especially in learning to identify the content of saga stories. Researchers use methodspre-experimental by using designone group pre-test post-test in conducting research. The research results show that learning to identify the content of saga stories using animation media meets the criteria for effectiveness. This is measured based on the results of the t test which shows a significance value of 0.000<0.05, which means H0 rejected and Ha accepted. Animation media that presents visualizations in the form of moving images accompanied by sound can increase students' focus in listening to saga stories.